Transcriptome analysis reveals ADAMTS15 is a potential inflammation-related gene in remote ischemic postconditioning - Zuo, Bo; Zhu, Sha; Wang, Guisong; Li, Zhengpeng (Frontiers in Cardiovascular Medicine, 2023)
Background Remote ischemic postconditioning (RIPostC) induced by brief episodes of the limb ischemia is a potential therapeutic strategy for myocardial ischemia/reperfusion injury, achieved by reducing cardiomyocyte death, inflammation and so on. The actual mechanisms underlying cardioprotection conferred by RIPostC remain unclear. Exploring gene expression profiles in myocardium at transcriptional level is helpful to deepen the understanding on the cardioprotective mechanisms of RIPostC. This study aims to investigate the effect of RIPostC on gene expressions in rat myocardium using transcriptome sequencing. Methods Rat myocardium samples from the RIPostC group, the control group (myocardial ischemia/reperfusion group) and the sham group were performed transcriptome analysis using RNA sequencing. The levels of cardiac IL-1β, IL-6, IL-10 and TNFα were analyzed by Elisa. The expression levels of candidate genes were verified by qRT-PCR technique. Infarct size was measured by Evans blue and TTC staining. Apoptosis was assessed by TUNEL assays and caspase-3 levels were detected using western blotting. Results RIPostC can markedly decrease infarct size and reduce the levels of cardiac IL-1β, IL-6 and increase the level of cardiac IL-10. This transcriptome analysis showed that 2 genes were up-regulated (Prodh1 and ADAMTS15) and 5 genes (Caspase-6, Claudin-5, Sccpdh, Robo4 and AABR07011951.1) were down-regulated in the RIPostC group. Go annotation analysis showed that Go terms mainly included cellular process, metabolic process, cell part, organelle, catalytic activity and binding. The KEGG annotation analysis of DEGs found only one pathway, amino acid metabolism, was up-regulated. The relative mRNA expression levels of ADAMTS15, Caspase-6, Claudin-5 and Prodh1 were verified by qRT-PCR, which were consistent with the RNA-seq results. In addition, the relative expression of ADAMTS15 was negatively correlated with the level of cardiac IL-1β (r=-0.748, P=0.005) and positively correlated with the level of cardiac IL-10 (r=0.698, P=0.012). A negative correlation statistical trend was found between the relative expression of ADAMTS15 and the level of cardiac IL-6 (r=-0.545, P=0.067). Conclusions ADAMTS15 may be a potential inflammation-related gene in regulation of cardioprotection conferred by remote ischemic postconditioning and a possible therapeutic target for myocardial ischemia reperfusion injury in the future.